Inhibition of stearoyl-CoA desaturase 1 in the mouse impairs pancreatic islet morphogenesis and promotes loss of β-cell identity and α-cell expansion in the mature pancreas - Aneta M. Dobosz; Justyna Janikiewicz; Ewelina Krogulec; Anna Dziewulska; Anna Ajduk; Marcin Szpila; Hanna Nieznańska; Andrzej A. Szczepankiewicz; Dorota Wypych; Agnieszka Dobrzyn (Elsevier, 2023)
Abnormalities that characterize the pathophysiology of type 2 diabetes (T2D) include deficiencies of β-cells and the expansion of α-cells in pancreatic islets, manifested by lower insulin release and glucagon oversecretion. The molecular mechanisms that determine intra-islet interactions between pancreatic α- and β-cells are still not fully understood. The present study showed that stearoyl-coenzyme A (CoA) desaturase 1 (SCD1), an enzyme that is implicated in fatty acid metabolism, serves as a checkpoint in the control of endocrine cell equilibrium in pancreatic islets. Our data showed that SCD1 activity is essential for proper α-cell and β-cell lineage determination during morphogenesis of the pancreas and the maintenance of mature β-cell identity. The inhibition of SCD1 expression/activity led to both a decrease in the expression of β-cell signature genes (e.g., Pdx1, Nkx6.1, MafA, and Neurod1, among others) and induction of the expression of the dedifferentiation marker Sox9 in mature pancreatic islets. The transcriptional repression of Pdx1 and MafA in SCD1-deficient β-cells was related to the excessive methylation of promoter regions of these transcription factors. In contrast, SCD1 ablation favored the formation of α-cells over β-cells throughout pancreas organogenesis and did not compromise α-cell identity in adult pancreatic islets. Such molecular changes that were caused by SCD1 downregulation resulted in the mislocalization of α-cells within the core of islets and increased the ratio of pancreatic α- to β-cell mass. This was followed by islet dysfunction, including impairments in glucose-stimulated insulin release, simultaneously with elevations of basal glucagon secretion. Altogether, these findings provide additional mechanistic insights into the role of SCD1 in the pathogenesis of T2D.